The Acceptance of Technology in Human Resource Management : Readiness e-HRD Among Healthcare Workers Using Binary Logistic Regression - Mellita, Dina; Zainal, Rabin Ibnu; Rafiansyah, M. Darrel (JINAV: Journal of Information and Visualization, 2023)
This research aims to identify the readiness of healthcare professionals in regional hospitals to use e-HRD technology. The use of technology in HRM functions is essential to maintain the efficiency and capabilities of human resources within an organization. E-HRD platforms are computerized systems that support the effective and efficient management of HR processes within an organization. To assess the efficiency of employing this technology, it is essential to determine the preparedness of the users. The Technology Readiness Index (TRI) proposed by Parasuraman is applied to assess healthcare workers' preparedness for using e-HRD. The UTAUT (Unified theory of acceptance and use of integrated technology) theory is employed to identify technological readiness. A quantitative descriptive research design is employed to identify the readiness of hospital healthcare workers. The data source for this research is primary data obtained through a questionnaire. The population in this study consists of 420 healthcare workers employed in regional hospitals in the city of Palembang. The sampling technique used in this research is proportional stratified random sampling. Logistic regression is employed to assess the preparedness of healthcare professionals in regional hospitals. The research findings indicate that male healthcare workers have a tendency to be 1.843 times more prepared to use e-HRD compared to female healthcare workers. The likelihood of healthcare workers using e-HRD tends to decrease by 0.002 times with increasing age. The research concludes that healthcare professionals in regional hospitals are moderately prepared to use e-HRD technology. The study recommends that healthcare organizations should provide training and support to enhance healthcare workers' readiness to use e-HRD technology.